2012
DOI: 10.3109/s10165-011-0516-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of adalimumab in Japanese patients with rheumatoid arthritis: retrospective analyses of data collected during the first year of adalimumab treatment in routine clinical practice (HARMONY study)

Abstract: We retrospectively investigated the ability of adalimumab (ADA) to reduce disease activity, improve physical function, and retard the progression of structural damage in 167 patients with rheumatoid arthritis. Clinical and functional outcomes were compared between patients with or without prior biologic treatment and those with or without concomitant methotrexate (MTX) treatment. At week 52, 38.3% achieved clinical remission: 42.4 and 28.6% of patients achieved remission in those without and with previous biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…Further, the percentage of patients reaching ACR20, ACR50, and ACR70 increased significantly during the 6-month period. In the retrospective study of Takeuchi et al investigating the ability of adalimumab to reduce disease activity in 167 patients with RA, the mean DAS28-ESR score decreased from 5.3 ± 1.3 at baseline to 3.5 ± 1.5 at week 52 ( p  < 0.0001), which is consistent with our findings [32]. …”
Section: Discussionsupporting
confidence: 92%
“…Further, the percentage of patients reaching ACR20, ACR50, and ACR70 increased significantly during the 6-month period. In the retrospective study of Takeuchi et al investigating the ability of adalimumab to reduce disease activity in 167 patients with RA, the mean DAS28-ESR score decreased from 5.3 ± 1.3 at baseline to 3.5 ± 1.5 at week 52 ( p  < 0.0001), which is consistent with our findings [32]. …”
Section: Discussionsupporting
confidence: 92%
“…In the present study, PWs at high risk of work disability showed significantly improved WPAI outcomes after treatment with ADA, as assessed by widely used WPAI/RA domain scores (absenteeism, presenteeism, OWI, and AI) [45, 46]. Significant decreases in DAS28CRP obtained in this real-world setting were consistent with those reported in clinical trials of 24- to 52-week duration, as well as a 24-week post-marketing surveillance study conducted in Japan [27, 39, 47, 48]. Importantly, in the present large-scale study, improvements in WPAI/RA showed a weak to moderately strong positive linear correlation with improvement in disease activity, extending the findings from a previous small-scale study assessing the effects of TNF-α antagonists on DAS28ESR and work productivity in 42 patients [15].…”
Section: Discussionsupporting
confidence: 77%
“…The differences in baseline HAQ-DI, EQ-5D-3L, and AI scores could be attributed to activity associated with employment status, as the dose of prednisolone, clinical disease activity measured by DAS28ESR, and SDAI were comparable at baseline between groups. Additionally, baseline characteristics of the patient population in this real-world study were heterogeneous in comparison to those of clinical trials in Japan [23, 26, 27, 39, 47, 48, 54]. Moreover, this study did not evaluate patients on the basis of comorbidity [54] and stage of disease, which could potentially impact the effectiveness of ADA.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is not specific to abatacept; similar data are available for other biological DMARDs [30,31]. Thus, a major challenge in RA management is the treatment of those with a prior history of biological DMARD use.…”
Section: Discussionsupporting
confidence: 54%